Parental exposure to Deepwater Horizon oil in different environmental scenarios alters development of sheepshead minnow (Cyprinodon variegatus) offspring. (September 2019) - Jasperse, Lindsay; Levin, Milton; Rogers, Kara; Perkins, Christopher; Bosker, Thijs; Griffitt, Robert J.; Sepúlveda, Maria S.; De Guise, Sylvain
Abstract: The explosion of the Deepwater Horizon (DWH) oil exploration platform on April 20, 2010 began a catastrophic leak of approximately 640 million liters crude oil into the northern Gulf of Mexico (GOM), affecting more than 2100 km of coastline, including wetlands and estuaries that provide habitat and nursery for many aquatic species. Estuaries of the GOM are dynamic environments, with constant fluctuations in salinity and dissolved oxygen, including large hypoxic zones during summer months. Spawning fish in northern GOM estuaries following the DWH incident were at significant risk of oil exposure, and adverse environmental conditions at the time of exposure, such as hypoxia and low salinity, could have exacerbated developmental effects in the offspring. The present study investigated the effects of F0 parental oil exposure in different environmental scenarios on development of F1 sheepshead minnow (SHM) offspring. Adult SHM were exposed to the high-energy water accommodated fraction (HEWAF) of crude oil in three environmental scenarios: normoxic (NORM), hypoxic (HYP), and hypoxic with low salinity (HYP-LS). Parental HEWAF exposure in the NORM scenario resulted in developmental effects in F1 offspring, including altered heart rate, decreased length at hatch, and impaired prey capture. Co-exposure of F0 SHM to HEWAF and adverse environmental conditions altered HEWAF effects on F1 heart rate, hatch rate, prey capture, and survival. Time to hatch was not significantly impacted by parental HEWAF in any environmental scenario. The present study demonstrates that parental exposure to HEWAF results in developmental changes in F1 embryos, and co-exposure to adverse environmental conditions altered the effects for several developmental endpoints. These data suggest that SHM exposed to oil in estuaries experiencing hypoxia or low salinity may produce offspring with worsened outcomes. These developmental effects, in addition to previously reported reproductive effects in adult fish, could lead to long-term population level impacts for SHM. Highlights: Eggs were collected from sheepshead minnow exposed to HEWAF in different scenarios. F0 exposure to HEWAF in normoxia altered embryo heart rate, length, and prey capture. F0 exposure to HEWAF in scenarios of environmental stress altered effects on embryos.